Crépe Amour Enterprise / Nurin Adriana Batrisyia Azhar ... [et al.]. - Azhar, Nurin Adriana Batrisyia; Zainois, Nur Izzati; Kamaruddin, Nur Aishah Al-Lisa; Azman, Nur Athirah (2025)
Created by a group of dessert lovers, Crêpe Amour is set to revolutionise the dessert market with its handcrafted pancake cakes that combine Malaysian flavours with French finesse. In 11th May 2023, Crêpe Amour, which is based in 10, Jalan Metro Ainsdale 3, Bandar Ainsdale,70200 Seremban, Negeri Sembilan, intends to formally begin operations. Creating sophisticated, delectable, and aesthetically pleasing desserts for a variety of events, including weddings, birthday celebrations, and business gatherings, is what drives our company. Five distinctive crêpe cakes are among our signature offerings: Classic Vanilla Elegance, Matcha Bliss, Belgian Chocolate Indulgence, Yoghurt Crêpe, and Tropical Fruit Crêpe, which features regional specialities like mango and durian. Each dish is genuinely unique since customers can add unique flavours, patterns, and decorative elements to theircrêpes. We offer whole cakes and slices to fit all kinds of needs. Also, we take orders for any occasion, such as weddings, birthdays, or events, as preferred by the customer. As for delivery, customers can either pick up their orders from the store or request delivery to their event venue or specified address.In order to keep our menu interesting and different, we will also be introducing limitededition and seasonal flavours. In order to meet important client needs, Crêpe Amour provides visually appealing desserts that are perfect for gatherings, balanced desserts that are neither too sweet nor heavy, and products with a two-to-three-day shelf life to reduce waste. In addition to addressing the market need for creative desserts that blend classic and contemporary flavours, our blend of regional flavours and global elegance guarantees a distinctive dining experience.